![](https://iknow-base.cdn.bcebos.com/lxb/notice.png)
分解因式:(1)-4+x2:(2)-4x2y+4xy2-y3;(3)9(a-b)2-4(a+b)2(4)3a2+bc-3ac-ab
分解因式:(1)-4+x2:(2)-4x2y+4xy2-y3;(3)9(a-b)2-4(a+b)2(4)3a2+bc-3ac-ab....
分解因式:(1)-4+x2:(2)-4x2y+4xy2-y3;(3)9(a-b)2-4(a+b)2(4)3a2+bc-3ac-ab.
展开
1个回答
展开全部
(1)原式=x2-4=(x+2)(x-2);
(2)原式=-y(4x2-4xy+y2)=-y(2x-y)2;
(3)原式=(3a-3b+2a+2b)(3a-3b-2a-2b)=(5a-b)(a-5b);
(4)原式=(3a2-3ac)+(bc-ab)=3a(a-c)-b(a-c)=(3a-b)(a-c).
(2)原式=-y(4x2-4xy+y2)=-y(2x-y)2;
(3)原式=(3a-3b+2a+2b)(3a-3b-2a-2b)=(5a-b)(a-5b);
(4)原式=(3a2-3ac)+(bc-ab)=3a(a-c)-b(a-c)=(3a-b)(a-c).
推荐律师服务:
若未解决您的问题,请您详细描述您的问题,通过百度律临进行免费专业咨询